Ana Clavel's "outlaw" desires in Las ninfas a veces sonríen. Issue 3 (1st September 2016) - Lavery, Jane Elizabeth
Abstract: As a writer whose fiction is known for its transgressive themes and forms, it is no surprise that the Mexican author Ana Clavel has continued to revel in such contraventions in her novella Las ninfas a veces sonríen (2012). In this article I seek to examine how these, also new transgressions, materialize in the novella specifically within a queer framework. The queer showcases Las ninfas ' exploration of "outlaw" sexual desires as well as the fantastical and intertextual genre-bending. By defying heteronormative sexual normalcy, Clavel is seen to challenge certain "givens" within (Mexican) society, whether these be religious, moral, sexual, or cultural, and thus creating a fascinating representation of society's particular fears, anxieties, and disavowed desires. In the context of the female character's sexual experiences, transgressive queereness can be understood by making reference to various theories including those of Kristeva's abjection/uncanny and Creed's/Braidotti's monstrous feminine, whereby the female is positioned in terms of an ambiguous oscillation between unthreatening object of male desire, monstrosity, and celebratory female sexual agency. Ultimately by thus delving into outlawed "no-deseos", Las ninfas can be posited as a prime example of a Barthesian text of "jouissance" which disrupts the reader's pleasurable reading experience.